EMPREENDEDORISMO SOCIAL E OPORTUNIDADES EMPREENDEDORAS SOCIAIS - Rodrigues dos Santos Pedroso, Débora Tayane (2021)
The aim of this article is to analyze the conceptual relationships between social entrepreneurship and social entrepreneurial opportunities from the bibliometric review as research strategies. To carry out this study, with a quantitative approach, exploratory and descriptive in nature, we used bibliometric research and the Proknow-C research method, using the VOSviewer software tool. The database chosen for this study was the Web of Science. The main results show that Neubaum, Zahra, Gedajlovic and Shulman are the most relevant authors and that the largest number of published documents are found in the USA. It appears that publications containing this theme are still scarce and recent, with the absence of documents published by Brazil in the Web of Science database, which can be considered as an emerging field of research and an area to be explored by Brazilian researchers. Furthermore, two perspectives present in the analyzed studies were identified: concepts and definitions of social entrepreneurship and social opportunities as a result of institutional voids.